Varying Effects of Temperature and Path-length on Ozone Absorption Cross-Section - Enenche Patrick; Michael David; A.O. Caroline; Mohd Haniff Ibrahim; Sevia Mahdaliza Idrus; Tay Ching En Marcus (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Inconsistencies in the absorption cross section of ozone have been observed. Hence, for accurate measurement, we have reported the combined effects of varying optical path-length and temperature on the ozone gas absorption cross section (OACS) at 334.15nm. Adopting optical absorption spectroscopy, results of the (OACS) have been simulated using spectralcalc simulator with HITRAN 12 has the latest line list. OACS increased by 52.27% as the temperature increased from 100K to 350K while it was slightly affected by a 0.007% decrease varying the path-length from 0.75cm-130cm.